2001
DOI: 10.3171/jns.2001.95.3.0432
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hearing loss after shunt placement in patients with normal-pressure hydrocephalus

Abstract: Although shunt insertion for treatment of NPH results in a decrease in hearing, most of the loss can be recovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
1
24
0
Order By: Relevance
“…This previously reported complication, 23 which is usually transient, appears to be permanent in my case.…”
Section: Clinical Medicine Vol 7 No 3 June 2007supporting
confidence: 52%
“…This previously reported complication, 23 which is usually transient, appears to be permanent in my case.…”
Section: Clinical Medicine Vol 7 No 3 June 2007supporting
confidence: 52%
“…137) Additionally, a study limited to iNPH patients reported improvement of symptoms in 55% of all cases with normal RI cisternography. 17) RI cisternography predicted shunt responsiveness less accurately than repeated lumbar CSF tap test or lumbar external CSF drainage, 61) and the use of RI cisternography did not add any additional information. 16) Because of the invasiveness and low diagnostic accuracy of CT or RI cisternography, it is not necessary for the diagnosis of iNPH (Recommendation grade C2); however, it may be useful in identifying obstructions in the circulation of CSF.…”
Section: -C Cisternographymentioning
confidence: 94%
“…56) In contrast, patency rates for Orbis-Sigma Valve } (Integra NeuroSciences, Sophia Antipolis, France) were lower than for the other tested valves and the rates of operation for subdural hematoma were higher than for the other valves. 66) Other reports of infrequent complications include gastrointestinal and bladder perforations from peritoneal catheters, 34) hearing deficits, 61) and tension pneumocephalus. 3) …”
Section: -B Complicationsmentioning
confidence: 99%
“…It has been suggested that ACs may cause a potentially abnormal elevated CSF pressure, which may lead to hearing loss, as observed in normal-pressure hydrocephalus [27] because intracranial pressure changes can be conducted to the inner ear via a patent cochlear aqueduct [28]. Furthermore, localized impingement of the AC on the eighth cranial nerve [16], and vascular compromise with interruption of the cochlear blood supply [29] have also been proposed as mechanisms of hearing loss.Another possible explanation would be a multifactorial cause.…”
Section: Discussionmentioning
confidence: 99%